Fake advertising? Neutrality in descriptions beside overall hotel scores - Mellinas, Juan Pedro; Reino, Sofia (Hospitality & Society, 2020)
Hotel reviews influence travellers' booking decisions. Research on this topic is focused on the scores or comments given through the reviews. However; no studies have looked reviews into the one-word descriptions associated with the overall scores received by hotels. This study examines this practice by conducting secondary research and identifying the one-word descriptions assigned to the different scores. The results suggest that each website providing average scores and one-word descriptions to summarize the scores uses a different policy to associate one-word descriptions to scores, suggesting lack of consistency. Furthermore, misleading practices have been identified, such as the use of the word 'average' to describe establishments with ratings lower than the midpoint of the scale. The findings have important implications both for the industry and for academia, as they highlight the need for transparent strategies and policies.
Keywords: average; average; descriptions; hotel; misleading; reviews; scores; Emerging; Scopus